2016
DOI: 10.1038/srep30606
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the gut microbiome of largemouth bronze gudgeon (Coreius guichenoti) suffering from furunculosis

Abstract: High-throughput sequencing was applied to compare the intestinal microbiota in largemouth bronze gudgeon either healthy or affected by furunculosis. Proteobacteria, Actinobacteria, Tenericutes, Firmicutes and Bacteroidetes were detected as the predominant bacterial phyla in the gut of both diseased and healthy fish. The abundance of Proteobacteria differed significantly between the two groups of fish, mainly due to the overwhelming prevalence of Aeromonas in the diseased fish (81% ± 17%), while the genus was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 54 publications
6
79
2
1
Order By: Relevance
“…In humans, reduced microbial diversity is associated with diseases such as obesity, type 2 diabetes (Brunak et al, ) and bowel disease (Shin, Whon, & Bae, ). Similarity, the bacterial diversity was markedly lower than in healthy fish (Li et al, ). The increase in microbial diversity in fish fed tributyrin supplementation of high‐SBM diet could be considered as reversing signs of intestine health.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In humans, reduced microbial diversity is associated with diseases such as obesity, type 2 diabetes (Brunak et al, ) and bowel disease (Shin, Whon, & Bae, ). Similarity, the bacterial diversity was markedly lower than in healthy fish (Li et al, ). The increase in microbial diversity in fish fed tributyrin supplementation of high‐SBM diet could be considered as reversing signs of intestine health.…”
Section: Discussionmentioning
confidence: 78%
“…PCoA showed that intestine content samples from fish that followed the same diet clustered together, although the SBM diet showed greater dispersion. As about the taxonomy community, no statistic difference in Proteobacteria relative abundance was observed among groups at phylum level, although imbalanced intestine microbiota often arises from a sustained increase in abundance of the phylum Proteobacteria (Li et al, ). However, within Proteobacteria, the SBM diet favoured the dominance of Acinetobacter over Brevundimonas , indicating the role of tributyrin in the regulation of intestine microbial composition.…”
Section: Discussionmentioning
confidence: 99%
“…) as well as in largemouth bronze gudgeon ( Coreius guichenoti ) and grass carp, which suffer from infections (Li et al . ; Tran et al . ), resulted in significant changes in gut microbiota.…”
Section: Factors Influencing the Formation Of Scfasmentioning
confidence: 99%
“…A recent study revealed that gut dysbiosis in Tsumura Suzuki obese diabetes (TSOD) mice leads to a reduction in total plasma SCFA levels, where acetate was decreased, with an increase in propionate and butyrate, while valerate and hexanoate were absent in the TSOD mice compared with controls (Nishitsuji et al 2017). In aquatic animals such as Atlantic salmon (Salmo salar) and Atlantic cod (Gadus morhua), supplementation with soybean-derived protein (Ringø et al 2006;Green et al 2013) as well as in largemouth bronze gudgeon (Coreius guichenoti) and grass carp, which suffer from infections (Li et al 2016;Tran et al 2018), resulted in significant changes in gut microbiota. It is unclear whether the changes of microbiota structure in these studies directly affected the levels of SCFA in the host gut.…”
Section: Factors Influencing the Formation Of Scfasmentioning
confidence: 99%
“…Disentangling the links between microbiome and fish health is a hot topic, particularly given the growth of the aquaculture industry. In this respect, the effects of pathogens, antibiotics and probiotics on microbiome composition have been subject of several studies showing that significant changes take place (e.g., Carlson, Leonard, Hyde, Petrosino, & Primm, 2017;Gonçalves & Gallardo-Escarate, 2017;Hennersdorf et al, 2016;Li et al, 2016;Llewellyn et al, 2017;Reid et al, 2017).…”
Section: Fish Microbiome: What We Knowmentioning
confidence: 99%